Direct production of biodiesel from waste oils with a strong solid base from alkalized industrial clay ash. (15th April 2020) - Cong, Wen-Jie; Wang, Yi-Tong; Li, Hu; Fang, Zhen; Sun, Jie; Liu, Hai-Tong; Liu, Jie-Teng; Tang, Song; Xu, Lujiang
Graphical abstract: Solid base synthesized from SBC ash for biodiesel production from waste oils with 8 cycles and anti-saponification. It was further magnetized for easy separation. Highlights: Direct production of biodiesel at 65 °C from waste oil by solid base was achieved. Solid base from alkalized SBC ash had basic sites from Na2 SiO3 and Na2 SiAlO4 . Biodiesel from soybean oil reached >99% yield with 8 cycles (>95%). Biodiesel yield was 96% from SBC oil (AV 10) at 65 °C ( vs . 120 °C with H2 SO4 ). It was magnetized for separation with biodiesel yield 99% for 3 cycles (87%). Abstract: Biodiesel was directly one-step produced from waste oils without pretreatment catalyzed by a solid base alkalized from spent bleaching clay (SBC) ash. Optimized conditions were obtained with 99.1% biodiesel yield from soybean oil with an orthogonal design. The base catalyst was stable within 8 cycles (>95% biodiesel yield) and resistant to saponification (AV = 9.7 mg KOH/g, 96.5% biodiesel yield). The base was characterized with XRD, EDX-mapping, FT-IR, XRF and TPD, and it had similar strong basicity to Na2 SiO3 (0.21 vs. 0.22 mmol/g for Na2 SiO3 ) with active sites of Na2 O and CH3 ONa evolved from Na2 SiO3 and NaAlSiO4 by reactions of NaOH with oxides (e.g., SiO2, Al2 O3 ) in SBC ash. Furthermore, the base was magnetized with magnetism of 6.86 emu/g by carbonizing residual oil in SBC as carbon support and reductant (of Fe2 O3 to magnetic Fe3 O4 particles). It catalyzed soybean oil to produce biodiesel with 99.2% yield and blended oil (AV = 5.9) to biodiesel with 91.9% yield without any saponification. The catalyst was magnetically separated and reused for 3 cycles with 87% yield. The non-magnetic base could also efficiently catalyze actual SBC oil for the production of biodiesel with 95% yield at AV of 10. This work realized the full use of inorganics in SBC, and its oil for direct biodiesel production at a low temperature (i.e., 65 vs. 120 °C with sulfuric acid process) without wastes produced and results can easily find practical applications for waste oils.